Clinicopathological characteristics and fertility preserving treatment of atypical polypoid adenomyoma - Wang, Qian; Shan, Weiwei; Yang, Bingyi; Xue, Yu; Lou, Yaochen; Chen, Xiaojun (Frontiers in Oncology, 2024)
Objective: This study aimed to investigate the clinical characteristics of atypical polypoid adenomyoma and the outcomes of conservative treatment in patients with APA. Methods: This retrospective single-center study analyzed 86 patients with APA treated at the Obstetrics and Gynecology Hospital of Fudan University between January 2010 and October 2021. Patients with EAH or EEC only who underwent fertility-preserving treatment during the same period were matched in a 2:1 ratio with patients with concurrent APA and EAH or EEC. The clinicopathological characteristics, treatments, and prognosis were analyzed.The median patient age was 31 years (range 21-47 years). Among the 86 included patients, nine underwent total hysterectomy, 62 received conservative treatment, and the remaining 15 were lost to follow-up. A comparison of the 16 patients with APA only versus the 58 patients with APA and concurrent or subsequent EAH or EEC revealed that a homeostasis model assessment of insulin resistance (HOMA-IR) of > 2.2 (P = 0.047) and high-density lipoprotein (HDL) concentration of < 1.2 mmol/L (P = 0.028) were independent risk factors for EAH or EEC in patients with APA. Among the 17 patients with APA only who received conservative treatment and achieved a CR after hysteroscopic lesion resection, 13 received hormone treatment for a median duration of 6.3 months. The median follow-up time for these 17 patients was 49.0 months, during which no recurrence of APA was observed, but six patients developed endometrial hyperplastic diseases. Regarding the impact of concurrent APA on fertility-preserving treatment for EAH or EEC, the median time to achieve a CR was 24.0 weeks (95% confidence interval [CI]: 23.0-40.4) in the APA group and 26.0 weeks (95% CI: 24.3-32.3) in the non-APA group (P = 0.424). There were no significant differences between the two groups in the outcomes of fertility-preserving treatment.Conclusions: Patients with APA only may still develop endometrial hyperplastic diseases after complete resection of the lesion under hysteroscopy to achieve a CR, particularly those with a HOMA-IR of > 2.2 or HDL concentration of < 1.2 mmol/L. Concurrent APA did not affect the efficacy of fertility-preserving treatment in patients with EAH or EEC.